PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN RESILIENSI SISWA KELAS X IPA SMA NEGERI 5 PEKANBARU - Uli bashirah Uli bashirah; Elni Yakub Elni Yakub; Raja Arlizon Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) to assess the resilience of students before being given guidance services group, 2) to assess the process of implementation guidance services group to increase the resilience of the students, 3) to determine the increase resilience students after being given guidance services group, 4) to determine differences in resilience students before and after the given group counseling services, 5) to determine how much influence the group counseling services to increase the resilience of the student. The method used is an experimental method to design one group pretest-posttest design. The subjects were students of class X IPA SMAN 5 Pekanbaru totaling 30 students. To collect the data used purposive sampling technique. To distinguish the resilience of students before and after the group guidance services using the test